(untitled) (Conferencea, 2023)
Energy drinks have become a ubiquitous part of modern life, offering an instant boost to alertness and energy. However, this article delves into the darker side of these beverages, exploring the negative effects they can have on human health. Drawing on insights from specialists and doctors, we examine the potential risks associated with excessive energy drink consumption, including impacts on cardiovascular health, mental well-being, and overall quality of life. This article aims to raise awareness about the dangers of energy drinks, highlighting the expert opinions and prohibitions surrounding their use.